HUMAN CAPITAL EXCELLENCE : HUMAN RESOURCE INVESTMENT AND GOVERNANCE IN IMPROVING THE COMPETITIVENESS OF ISLAMIC BANKING EMPLOYEES (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2025)
Islamic banking in Indonesia faces significant challenges in managing competitive human capital (HC), despite its rapid development in line with the growing awareness of Sharia-based finance. This study aims to analyze the effect of human capital investment, namely salary and training, on employee performance in Islamic commercial banks, and to examine the role of Good Corporate Governance (GCG) as a moderating variable. The research employs a quantitative approach using panel data from seven Islamic commercial banks over a ten-year period (2015–2024), analyzed with multiple regression and Moderated Regression Analysis (MRA) through EViews software. The results reveal that salary has a significant effect on employee performance, while training shows no significant impact. Furthermore, GCG significantly influences performance and strengthens the effect of salary on performance, but does not moderate the relationship between training and performance. These findings indicate that financial compensation supported by sound governance is a key factor in enhancing employee productivity and competitiveness, whereas the effectiveness of training still requires improvement in terms of planning and implementation. In conclusion, the application of GCG principles is not only crucial as a governance instrument but also strategic in optimizing human capital investment aligned with Sharia values, thereby providing a foundation for managerial policies of Islamic banks as well as regulators to strengthen sustainability and competitive advantage in Indonesia’s Islamic banking sector.